Wind Turbine Fault Detection System in Real Time Remote Monitoring - Saad Chakkor; Mostafa Baghouri; Abderrahmane Hajraoui (International Journal of Electrical and Computer Engineering (IJECE), 2014)
In new energy development, wind power has boomed. It is due to theproliferation of wind parks and their operation in supplying the nationalelectric grid with low cost and clean resources. Hence, there is an increasedneed to establish a proactive maintenance for wind turbine machines based on remote control and monitoring. That is necessary with a real-time wireless connection in offshore or inaccessible locations while the wired method has many flaws. The objective of this strategy is to prolong wind turbine lifetime and to increase productivity. The hardware of a remote control and monitoring system for wind turbine parks is designed. It takes advantage of GPRS or Wi-Max wireless module to collect data measurements from different wind machine sensors through IP based multi-hop communication. Computer simulations with Proteus ISIS and OPNET software tools have been conducted to evaluate the performance of the studied system. Study findings show that the designed device is suitable for application in a wind park.DOI:http://dx.doi.org/10.11591/ijece.v4i6.6479